Moving Beyond the Neck and Arm: The Pain Experience of People With Degenerative Cervical Myelopathy Who Have Pain. Issue 7 (September 2022) - Boerger, Timothy; Alsouhibani, Ali; Mowforth, Oliver; Hamilton, Joseph; Lalkhen, Abdul; Davies, Benjamin M.; Kotter, Mark R. N.
Study Design: Cross-sectional internet survey of people living with degenerative cervical myelopathy. Objective: The purpose of this study was to quantify pain distribution, severity, and interference in persons with degenerative cervical myelopathy. Methods: Eighty-two participants with degenerative cervical myelopathy were recruited for this internet survey. This survey utilized the Michigan Body Map and brief pain inventory (BPI) to assess anatomical distribution and severity of pain as well as the patient derived modified Japanese Orthopedic Association scale (p-mJOA) for myelopathic severity and SF-36 for measures of health-related quality of life. Internal consistency was evaluated with Cronbach's alpha. Pearson's correlations were assessed with p-mJOA and SF-36. Multivariate analysis of variance was used to determine if history of prior surgery or concomitant pain diagnosis impacted experience of pain. Results: Michigan body map distribution and brief pain inventory severity and interference were correlated with p-mJOA and SF-36 scores (p < 0.05). Pain was moderate to severe in 78% of participants. Pain was commonly widespread. Pain scales were sufficiently internally consistent (α > 0.9). History of surgery or other pain diagnosis did not impact experience of pain in myelopathy. Conclusions: Pain is commonly identifiable in large areas of the body, is frequently moderate to severe in intensity and impacts quality of life and severity of myelopathy in a cohort of individuals with myelopathy who have pain.